Philippians - Fee, Gordon D. (Downers Grove, Ill. : InterVarsity Press, 1952)
In Philippi, Paul addressed a congregation whose private internal struggles were compounded by opposition and suffering from without. Paul's strategy was to write them a letter of friendship and moral exhortation, reminding them of their "partnership in the gospel," their mutual suffering for the cause of Christ, and their need to "stand firm in one spirit."--Publisher description.
Introduction -- Outline of Philippians -- Commentary.
Includes bibliographical references (pages 199-204).
Keywords: Bible. -- Commentaries